Case Report: 7-year-old boy with incarcerated internal hernia leading to extensive intestinal necrosis due to a large congenital mesenteric defect - Deeg, Susanne; Krickeberg, Sophie; Nisar, Tauseef; Schwarz-Bundy, Bogáta D.; Wessel, Lucas (Klinische Pädiatrie, 2021)
We present a case of a 7-year-old boy with acute abdominal symptoms initially misdiagnosed as constipation. Delayed imaging diagnostics revealed an ileus with contorted small intestine, so laparotomy was indicated. An acute bowel obstruction was found based on an incarcerated internal hernia. Small and large bowel segments were incarcerated into a large mesenteric defect leading to extended intestinal necrosis. About 30 cm of necrotic small bowel and 15 cm of large intestine were resected, two primary anastomoses were performed. The mesenteric defect was closed with two running sutures. The boy’s clinical outcome was very good. Two aspects are discussed: the initial clinical misdiagnosis of acute bowel obstruction in a child leading to a delay of diagnostics and therapy on the one hand and the origin of mesenteric defects on the other. In children with abdominal pain, ultrasound must be performed as soon as possible and pediatric surgeons have to be involved early. There should be an awareness of the fact, that mesenteric defects and other congenital malformations can occur more often than we suspect it. In the case of an internal hernia, a misjudgement of the clinical condition may be very harmful for the patient and can lead to a short bowel syndrome or even death.